Status Kadar Kolesterol Terhadap Kebiasaan Orang Yang Mengonsumsi Teh - Nur Vita Purwaningsih (THE JOURNAL OF MUHAMMADIYAH MEDICAL LABORATORY TECHNOLOGIST, 2020)
ABSTRACT Lifestyle must be a trend nowadays, many high cholesterol foods needed in daily life can increase blood cholesterol and increase the risk of cardiovascular disease. One way to reduce cholesterol in the body is by consuming tea. Tea has a very beneficial content for the body. One of the contents of the tea is catechins. Catechins are secondary metabolites that are naturally produced by plants belonging to the flavonoid class, which are made to help absorb calcium in the intestine. This type of research is observational analytic samples collected are students who have the habit of consuming tea by doing two examinations that is before and observing observations for 3 months. Based on the results of the study obtained an average cholesterol level before the observation of the results obtained 152.9 mg / dl while for the temporary examination of the results obtained 141.3 mg / dl. The results of data analysis using the Paired T Test with sig 0.00 which means less than 0.05. So, it can be concluded that there is an influence of tea consumption habits on cholesterol levels. Keywords: cholesterol, habits in consuming tea